Attitudes, Preferences and Usage Behavior of the Population Regarding Social Media Pages of Hospitals - Results of a Quantitative Survey in the DACH Region (Germany, Austria, Switzerland) - Michael Beier; Sebastian Früh (ZBW - Leibniz Information Centre for Economics, 2021)
This research report describes attitudes, preferences and usage behavior of the population regarding social media pages of hospitals. For this purpose, the results of a quantitative survey (N=1,547) in the DACH region (Germany, Austria, Switzerland) are presented and explained.
Keywords: 330; social media; hospitals; digital health; preferences; usage behavior; Facebook; Twitter; Instagram; LinkedIn; XING; YouTube